2005
DOI: 10.1152/jn.01303.2004
|View full text |Cite
|
Sign up to set email alerts
|

Arm Movements Evoked by Electrical Stimulation in the Motor Cortex of Monkeys

Abstract: Electrical stimulation of the motor cortex in monkeys can evoke complex, multijoint movements including movements of the arm and hand. In this study, we examined these movements in detail and tested whether they showed adaptability to differing circumstances such as to a weight added to the hand. Electrical microstimulation was applied to motor cortex using pulse trains of 500-ms duration (matching the approximate duration of a reach). Arm movement was measured using a high-resolution three-dimensional trackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
138
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 47 publications
16
138
1
Order By: Relevance
“…Our data support the finding that HFLD-ICMS at a particular cortical site produces movements of the forelimb toward a final common end-point position independent of the starting position (Graziano et al, 2002;Graziano et al, 2005). We also found that muscle activation associated with HFLD-ICMS is largely stable in sign, magnitude, and temporal pattern independent of starting position or arm posture.…”
Section: Discussionsupporting
confidence: 87%
“…Our data support the finding that HFLD-ICMS at a particular cortical site produces movements of the forelimb toward a final common end-point position independent of the starting position (Graziano et al, 2002;Graziano et al, 2005). We also found that muscle activation associated with HFLD-ICMS is largely stable in sign, magnitude, and temporal pattern independent of starting position or arm posture.…”
Section: Discussionsupporting
confidence: 87%
“…In this light, it is important to consider that control potentials are revealing the effects of only one component signal in the broader motor programme. Showing how these specific causal relationships are combined, perhaps nonlinearly, into synergies [24,56,57] or motor primitives [22,58], or how they remain flexible, distinct elements [57,59] will test how specific muscles contribute to a control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for the importance of kinematic parameters in the generation of reaching movements was provided by direct stimulation of the motor cortex (Graziano, Aflalo, & Cooke, 2005;Graziano, Taylor, & Moore, 2002). These studies imply one-toone mappings between workspace and arm posture located in the motor cortex.…”
Section: Relation To Neurophysiological Evidencementioning
confidence: 93%